ADSORPTION OF Cr(VI) ON BLACK WATER - Rasti Januarita; Herdiansyah Herdiansyah (Universitas Gadjah Mada, 2003)
The effect of initial concentration of Cr(VI) on adsorption to black water of Gambut, District of Banjar, South Borneo has been investigated, as well as interaction between Cr(VI) species and functional black water organic fraction.The initial work was optimization of Cr(VI) determination using UV-Visible Spectrophotometry with diphenylcarbacide as complexing agent and preparation of black water using mixture of 2% HCl and 5% HF with HCl-HF ratio of 1 : 1 (v/v). The quantity of Cr(VI) species adsorbed on black water was calculated by determining the amount of Cr(VI) species in solution before and after interaction. The functional groups in interaction between Cr(VI) species and black water organic fraction was studied qualitatively using infrared spectroscopy.The results showed that optimum condition for Cr(VI) species analysis using UV-Visible spectrophotometry with diphenylcarbacide as complexing agent was at wave length of 540 nm, pH 1,5, 15 - 60 minutes at which complex remain stable, and minimum mol ratio of diphenylcarbacide : Cr(VI) 45 : 1, and has a sensitivity of 1.134 mg/L and detection limit of 0.00495 mg/L. The analysis was not affected by the presence of Cr(III) in concentration less than 40 times of Cr(VI) concentration. After treatment with HCl-HF the quantity of black water organic fraction showing humic acid properties decreased 0,1998 percent. Organic fraction of black water used adsorpted Cr(VI)with capacity of 4,050 mg/g.